Application of Progressive Muscle Relaxation Therapy in Overcoming Nurse's Work Stress in Depok City Regional General Hospitals - Tatiana Siregar; Andal Izah Rabani (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Every nurse who works in a hospital will face quite time-consuming and laborious work, especially when the bed occupancy rate (BOR) is 85%, and the work pressure of nurses is high. The effect of work stress manifests as physical fatigue, psychological changes, and behavioral changes. Nurses need to try to prevent work stress from happening for a long time by doing stress management, one of which is progressive muscle relaxation therapy. Objectives: The purpose of the study was to determine the effect of progressive muscle relaxation therapy in reducing nurses’ work stress. Methods: The study was conducted on five resident nurses who were trained using Progressive Muscle Relaxation and then used the Nursing Stress Scale to measure stress levels before and after training. The research design was Quasi Experiment with One group pretest and post-test designs; data analysis with paired t-test. Results: The results showed that there was a significant effect of implementing progressive muscle relaxation therapy on reducing nurse work stress (p = 0.024; 95% CI). Conclusion: There is a significant effect of progressive muscle relaxation therapy on the work stress response of nurses. Progressive muscle relaxation therapy is good to apply to hospital nurses who go through work stress so that stress does not occur which can risk reducing the quality of service to patients.